Effects of methyl jasmonate and phloroglucinol on thebaine and sanguinarine production in cell suspension culture of Persian poppy (Papaver bracteatum Lindl.) - Dastmalchi, Taraneh; Omidi, Mansour; Azizinezhad, Reza; Rezazadeh, Shamsali; Etminan, Alireza (Cellular and Molecular Biology, 2019)
The biosynthesis path engineering could be very promising for mass production of alkaloids by applying elicitors in the cell suspension culture of Persian poppy (Papaver bracteatum Lindl.). In this work, the effects of different concentrations of methyl jasmonate (MJ) and phloroglucinol (PG) on thebaine and sanguinarine productions in vitro were investigated. Roots as explant and supplementing 3 mg L–1 2,4-Dichlorophenoxyacetic acid with 0.5 mg L–1 Benzyl amino purine to modified MS medium were selected to achieve the most efficient combination for callus induction and production of callus fresh and dry weights. At 48 h after treatment, the addition of PG and MJ individually and in combination together significantly increased both thebaine and sanguinarine contents than the control. The results of high-performance liquid chromatography (HPLC) detection indicated that the highest production rate has been achieved through a synergic effect of two elicitors after 48 h. Results revealed that adding 200 Î¼M of MJ and 100 mg L–1 PG increased thebaine and sanguinarine contents by 56.36 and 107.71–fold than control cells, respectively.